Objectivity and the Scientific Study of Religion - Thoha, Anis Malik (Intellectual discourse, 2009)
The concern for and the debate on "objectivity" in the scientific study of religions led scholars to advocate two major approaches known as "History of Religion" and "Phenomenology of Religion." Both approaches are claimed to be "descriptive" and "value-free" as they stringently enforce the principle of epochê or distanciation to ensure objectivity. However, there are scholars who argue that objectivity (be it "descriptive" or "value-free") is ontologically questionable and epistemologically impossible. It is a selfdefeating concept and a myth. They argue that objectivity is principally and directly concerned with "the object" under investigation regardless of the types of approach used.